Strategi Reformasi Administrasi dan Kepemimpinan Strategies Admisnistrative Reforms and Leadership - Ramadhani Haryo Seno (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2020)
This paper seeks to explain the administration and leadership reform strategy. Administrative reform and leadership are two things that are interrelated and inseparable. Leadership in government requires administrative reform to increase the legitimacy of its government. On the other hand, administrative reform requires commitment and consistency of leadership to ensure its success goals are achieved. Administrative reform is something that is ongoing and sustainable, but without the right administrative reform strategy it is clearly difficult to get the desired results. In other words, the right strategy will determine the success of the implementation of administrative reform. Especially if the implementation of this administrative reform is supported by the commitment of the national leadership all out.